Role of microbial communities and nitrogen sources in suppressing root rot disease during ginseng cultivation - Cho, Gyeongjun; Kim, Da-Ran; Kwak, Youn-Sig (Frontiers in Microbiology, 2024)
Ginsengs, widely acknowledged for their health-promoting properties, are predominantly grown for their roots, necessitating an extended cultivation period of a minimum of 4 to 6 years for maturation. The prolonged growth duration in a specific location makes ginseng plants susceptible to soil-borne ailments, such as root rot, leading to significant detrimental effects. Focusing on the crucial role of the plant microbial community in maintaining ginseng health, the study reveals that repeated and continuous cultivation leads to the collapse of the initial disease-suppressive rhizosphere community, resulting in severe root rot. The dominance of Pseudomonadaceae in the rhizosphere subsequently reinstates disease suppression, aligning with suppressive soil generation phenomena. The research investigates the applicability of identified patterns to field conditions and demonstrates that rhizosphere samples from the field closely resemble conditions observed in pot-based NH4Cl treatment experiments. These findings emphasize the critical role of the rhizosphere microbial community in ginseng health maintenance during extended cultivation, offering insights into disease prevention strategies. The study also suggests the potential of pot-based experiments in simulating field conditions and informs future approaches for sustainable ginseng cultivation.